THE SOCIO-CULTURAL ASPECTS OF NORMING SEXUALITY (Годишен зборник на Филозофски факултет - Скопје, 2025)
Even with the act of birth, we, as human beings are “assigned” different” identitiesthat differ from our wishes. The same identities that we are assigned at birth continueto be further moulded and shaped through the process of socialization. Even so,sometimes we even discredit or “give up” on those identities entirely. The focal point ofthis thesis is placed upon the human sexuality, culture, and society, and the ways thesocio-cultural context influence the shaping of human sexuality. Hence, my efforts tohirghlight the enormous influence of the culture over the modelling of the human sexuality.In fact, the aim of this academic presentation is to discredit the traditional claims(that do not possess evidence of the claim) that sexual desire, i.e., sexuality as a whole, istreated as a kind of given or genetically predisposed occurrence (also referring to heterosexualityas the sole, healthy sexual desire). In the same notion, I intend to unveil theinfluence of the social and cultural factors in the shaping of the sexual behaviour, whichare rather significant factors that have been greatly ignored throughout history. Thesexual behaviours of people hold certain meanings – people use and express their sexualityin a variety of ways. To people, there is more to sexual activity than just biology. Inthat context, we shall consider culture as the rudimentary determinant in the process ofthe formation of human sexuality. In the light of such occurrences, the need for a moreexact examination of the role of the culture in the shaping of human sexuality arises.Besides impacting the shape of human sexuality, culture is an inevitable influencer ofthe gender self-identification in time and space.